REACTOGENICITY OF ACELLULAR PERTUSSIS VACCINE AND THE POSSIBILITY OF ITS USE IN ELDER CHILDREN - M.G. Galitskaya; L.S. Namazova; M.V. Fedoseenko; A.G. Gaivoronskaya; S.G. Aleksina (Педиатрическая фармакология)
As is know, in the past few years, the incidence of pertussis has increased again. The article reveals the reasons of this phenomenon and the possible solutions for this problem. Besides, comparative analysis of the whole cell vaccine used in this country as within the framework of the national immunizations schedule and modern acellular vaccines is made. Results of multicenter research, convincingly proving the safety and efficiency of acellular pertussis vaccine, are presented.Key words: pertussis, prophylaxis, whole cell vaccine, acellular vaccine, efficiency, children.